Controlling system in-house staff training - P. .. Ananchenkova (Путеводитель предпринимателя)
The paper presents the analysis of the system of controlling the effectiveness of the implementation of in-house training programs. Determined the content of the notion of controlling, its aims, tasks, tools and processes.